Dual kinetics of OATP2B1: Inhibitory potency and pH-dependence of OATP2B1 inhibitors. (December 2021) - Sato, Ryo; Akiyoshi, Takeshi; Morita, Tokio; Katayama, Kazuhiro; Yajima, Kodai; Kataoka, Hiroki; Imaoka, Ayuko; Ohtani, Hisakazu
Abstract: Organic anion transporting polypeptide (OATP) 2B1 is expressed in the intestine and liver, and OATP2B1-mediated transport of estrone 3-sulfate is pH-dependent and consists of: the high-affinity component (Hc) and low-affinity component (Lc). This study aimed to evaluate the influence of pH on the transport kinetics of each component, along with the inhibitory nature of ten OATP2B1 inhibitors. The Michaelis constants ( K m ) were 4-fold and 1.5-fold lower at pH 6.3 than at pH 7.4, for Hc and Lc respectively. The inhibitory potencies of diclofenac, indomethacin, and ibuprofen towards Hc were 1.5–4.3 fold lower at pH 6.3 than at pH 7.4. Contrastingly, inhibitory potencies towards Lc were 9.0–52 fold lower at pH 7.4. Similarly, the inhibitory effect of naproxen was stronger towards Hc at pH 6.3 and towards Lc at pH 7.4. On the other hand, celecoxib selectively inhibited Lc transport at pH 7.4. Rifampicin inhibited both components at pH 6.3 and 7.4 to a similar extent, while bromosulphophthalein, naringin, and gefitinib selectively inhibited Hc irrespective of pH. Fexofenadine inhibited neither component. In conclusion, the transport affinities of both Hc and Lc were enhanced under acidic conditions. The influence of pH on the inhibitory potency towards each component varied among the inhibitors.